Morphology and Anatomy of Marsilea Minuta L. - A Common Pteridophyte Found In Kota University Campus Kota, Rajasthan India - Dr Shivali Kharoliwal, (International Journal of Scientific Research in Science and Technology, 2025)
Genus Marsilea is well known for its morphological plasticity, commonly known as water clove face interesting diversified status due to their variable climatic conditions.Marsilea minuta Linn.. an aquatic or sub-aquatic heterosporous fern which grows in less moist areas is of University campus, Kota .The present work was undertaken with the specific aim of studying morphology and anatomy of wild population of Marsilea species found in University Campus Kota Rajasthan India .
Keywords: Marsilea; Morphology; Pteridophytes